Sentidos da escola de tempo integral na vivência de alunos de uma escola estadual: uma investigação sobre o ficar na escola o dia todo - Barros, Emília Cristina Ferreira de (2012)
The perspective of this study was to analyze the impact of proposed school full time and bring to the field of research the experience of young people enrolled in a school in two shifts. The study focused on the More Education Program (2007), the federal government, created under the aegis of the assumptions of LDB/1996, which provides progressive extension of the school day, including as belonging to the emergency context of this proposal, the Children and Adolescents, established in 1990, and the National Plan for Human Rights Education (PNEDH), launched in 2003, in a clear alliance between the educational and social principles. The 24 students who participated in the survey were asked to construct images that represented their relationship with the "stay in school all day." The material produced and presented speeches opposing images demonstrating a strong field of confrontation. In most designs the school was identified as an area imprisoning, exemplified with grids and other forms of representation of incarceration, aspects of nature and pictures of sad children. In other drawings were observed images of dissatisfaction, while appearing indications of contentment and hope and improvement proposals. The images and texts of the students were analyzed using as a counterpoint legal documents justifying the program and instruct the extension of the school day. Conceptions of educational policies, vulnerability, risk and social rights were problematized in light of the analyzes, which indicate a sense of normalization of differences and social control policies of inclusion.